Polymicrogyria: A common and heterogeneous malformation of cortical development. Issue 2 (28th May 2014) - Stutterd, Chloe A.; Leventer, Richard J.; Mirzaa, Ghayda M.; Paciorkowski, Alex R.
<x xml:space="preserve">Abstract</x> Polymicrogyria (PMG) is one of the most common malformations of cortical development. It is characterized by overfolding of the cerebral cortex and abnormal cortical layering. It is a highly heterogeneous malformation with variable clinical and imaging features, pathological findings, and etiologies. It may occur as an isolated cortical malformation, or in association with other malformations within the brain or body as part of a multiple congenital anomaly syndrome. Polymicrogyria shows variable topographic patterns with the bilateral perisylvian pattern being most common. Schizencephaly is a subtype of PMG in which the overfolded cortex lines full‐thickness clefts connecting the subarachnoid space with the cerebral ventricles. Both genetic and non‐genetic causes of PMG have been identified. Non‐genetic causes include congenital cytomegalovirus infection and in utero ischemia. Genetic causes include metabolic conditions such as peroxisomal disorders and the 22q11.2 and 1p36 continguous gene deletion syndromes. Mutations in over 30 genes have been found in association with PMG, especially mutations in the tubulin family of genes. Mutations in the (PI3K)‐AKT pathway have been found in association PMG and megalencephaly. Despite recent genetic advances, the mechanisms by which polymicrogyric cortex forms and causes of the majority of cases remain unknown, making diagnostic and prenatal testing and genetic counseling challenging. This review summarizes the clinical, imaging, pathologic, and etiologic features of PMG, highlighting recent genetic advances. © 2014 Wiley Periodicals, Inc.